INDUKSI ESTRUS DENGAN PMSG DAN GN-RH PADA SAPI PERAH ANESTRUS POSTPARTUM - Pemayun, Tjok Gde Oka (Buletin Veteriner Udayana, 2012)
This study was conducted to observe the effect of Gn-RH and PMSG on onset of oestrusin the postpartum anoestrus dairy cattle. The total of twenty one postpartum anoestrus dairycattle for used for this study. They were divided into three groups i.e. (I) treated with singledose injection of 500 ug Gn-RH /im/head (Gn-RH 1x), (II) treated with twice injection 250ug Gn-RH/im/head (at 24 hours interval) (Gn-RH 2x), and (III) treated with single doseinjection of 1000 IU PMSG/im/head. The result showed that the onset of oestrus wichtreated with PMSG was earlier (3,43 ± 0,79 days) than Gn-RH 1x (7,17 ± 3,24 days). Incoclusion, The PMSG was as effective as Gn-RH to the onset of oestrus
Keywords: Gn-RH; PMSG; postpartum anoestrus; dairy cattle